MANAJEMEN RISIKO, KUALITAS CORPORATE GOVERNANCE, STATUS KEUANGAN PERUSAHAAN, DAN PERILAKU OPPORTUNISTIK MANAJERIAL - Kamaludin, Kamaludin; Nikmah, Nikmah; Hijroini, Hijroini (UNIB Press, 2015)
This study aims to examine the causal relationship between the variables of risk management, the financial status of the company, the quality of corporate governance and managerial opportunistic behavior. Risk management is measured by current ratio, the company's financial status is measured by Altman Z Score bankruptcy prediction, such as the quality of corporate governance Corporate Governance Perception Index (CGPI) while conducting managerial opportunistic behavior pattern of earnings management is proxied by Eckel Index (1981). Testing is done with path analysis (path analysis) with the help SmartPLS 1.10 versions in 47 companies listed on the Indonesian Institute of Corporate Governance (IICG) 2011-2013 and submit an annual report on the Indonesia Stock Exchange (IDX). This study found that the risk management and financial status of the company does not have an influence on managerial opportunistic behavior. While the quality of corporate governance can reduce managerial opportunistic behavior. Risk management is a negative impact on the quality of corporate governance while financial status may have an impact on the quality of corporate governance. Risk management had a positive influence to the company with a sound financial status. In path analysis, risk management is not directly influence on managerial opportunistic behavior. But risk management can improve the financial status of the company's reputation and raise the quality of corporate governance, so as to suppress the manager to perform income smoothing. On the one hand, managers still perform income smoothing though the company has a risk management and corporate governance, since the motivation that is efficient to perform earnings management. In this case, financial status and corporate governance becomes an intervening variable.